2013
DOI: 10.1007/s10753-013-9725-9
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Inhibits Interleukin-1β-Induced Proliferation of Human Rheumatoid Arthritis Fibroblast-like Synoviocytes

Abstract: Baicalein shows anti-inflammatory effects in human rheumatoid arthritis fibroblast-like synoviocytes (RAFLS). Considering its anti-proliferatory effects on various cancer cells, we investigated the effects of baicalein on interleukin-1 beta (IL-1β)-induced proliferation of human RAFLS. Cell proliferation was examined by (3)H-thymidine incorporation assay. Western blot analysis was performed to assess the phosphorylation of extracellular regulating kinase (ERK), p38, and c-Jun N-terminal kinase, and nuclear tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…Therefore, these results together with our findings suggest that the induction of CD4 + Foxp3 + Tregs by baicalein-mediated AhR activation might suppress the function of other CD4 + T cells such as Th1, Th2, and Th17. Our results were also consistent with those of previous reports, which reported the efficacy of baicalein in the treatment of atopic dermatitis (Th2-Th1 response), colitis, and rheumatoid arthritis (Th1-Th17 response)394041.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, these results together with our findings suggest that the induction of CD4 + Foxp3 + Tregs by baicalein-mediated AhR activation might suppress the function of other CD4 + T cells such as Th1, Th2, and Th17. Our results were also consistent with those of previous reports, which reported the efficacy of baicalein in the treatment of atopic dermatitis (Th2-Th1 response), colitis, and rheumatoid arthritis (Th1-Th17 response)394041.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, some studies have demonstrated the effects of baicalein on cisplatin sensitivity via different pathways in various cancer cells . Baicalein has also exhibited a wide range of anti‐inflammatory effects associated with airway injury, liver injury and rheumatoid arthritis . In summary, baicalein has the potential to become an ideal adjuvant therapy in the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 There is also evidence that baicalein may exert its effects via the PTEN/Akt pathway. 22,33 MicroRNAs (miRNAs) are small non-coding RNAs with lengths of [19][20][21][22][23][24][25] nucleotides that regulate the translation or degradation of target mRNA in the human body. 34 MiRNAs play an important role in the proliferation, invasion and apoptosis of malignant tumour cells and may affect resistance to cisplatin.…”
mentioning
confidence: 99%
“…In additon, baicalein has been shown to attenuate MMP-1 expression in human keratinocytes [11]. Furthermore, baicalein has been reported to inhibit the proliferation of human rheumatoid arthritis fibroblast-like synoviocytes [12]. Whether baicalein possesses antiosteoarthritic properties remains unknown.…”
Section: Introductionmentioning
confidence: 99%